Consultative Leadership: Strategies for Improving Cognitive-Emotional Wellbeing to Reduce Short Attention Spans in Students - Evi Susiyanti (Universitas Pendidikan Mandalika, 2025)
This study aims to analyze the role of consultative leadership in creating effective schools and its contribution to reducing students' short attention span through improving cognitive-emotional wellbeing. This study uses a quantitative approach with a Structural Equation Modeling (SEM) design assisted by SmartPLS 3. The research sample consisted of 11th grade students from four public high schools in Pasuruan City, selected through simple random sampling. The results show that consultative leadership has a significant effect on cognitive-emotional wellbeing in reducing short attention span. Simultaneously, the variables of consultative leadership and cognitive-emotional wellbeing contribute 23.6% to the reduction in short attention span. These findings emphasize the importance of effective schools and strengthening cognitive-emotional wellbeing as key strategies for improving students' learning focus, while consultative leadership plays a stronger role in building a collaborative culture in schools. Keywords: consultative leadership, cognitive-emotional wellbeing, short attention span Abstrak (Indonesia): Penelitian ini bertujuan menganalisis peran kepemimpinan konsultatif dalam menciptakan sekolah yang efektif serta kontribusinya dalam mengurangi short attention span peserta didik melalui peningkatan cognitive-emotional wellbeing. Studi ini menggunakan pendekatan kuantitatif dengan desain Structural Equation Modeling (SEM) berbantuan SmartPLS 3. Sampel penelitian adalah siswa kelas XI dari empat SMA Negeri di Kota Pasuruan yang ditentukan melalui simple random sampling. Hasil penelitian menunjukkan bahwa kepemimpinan konsultatif berpengaruh terhadap cognitive-emotional wellbeing signifikan dalam menurunkan short attention span. Secara simultan, variabel kepemimpinan konsultatif, cognitive-emotional wellbeing memberikan kontribusi sebesar 23,6% terhadap penurunan short attention span. Temuan ini menegaskan pentingnya peran sekolah efektif dan penguatan wellbeing kognitif-emosional sebagai strategi utama untuk meningkatkan fokus belajar peserta didik, sementara kepemimpinan konsultatif berperan lebih kuat dalam membangun budaya kolaboratif di sekolah. Kata Kunci: kepemimpinan konsultatif, cognitive-emotional wellbeing, short attention span